Financial cooperation for development, DNA of South-South Cooperation - Domínguez-Martín, Rafael (Iberoamerican Journal of Development Studies, 2016)
The aim of this article is to assess the weight and implications of the refundable component of financing for development offered by China. The relevance of focusing on the reimbursable financial cooperation of China derives not only from its quantitative importance, but of two qualitative aspects that contribute to a fuller understanding of SCC in general: reimbursable financing is the basis on which the dialogue pillar rests characteristic of the SCC, which, since its inception, sought to forge alliances for change in international economic relations policy; and reimbursable financial cooperation, as true SSC’s DNA, marks the trend towards the financing of the new agenda of Sustainable Development Goals has been headed.
Keywords: South-South cooperation; repayable cooperation; financial cooperation; Chinese cooperation